The Influence of Brand Image and Brand Trust on the Decision to Purchase Le Minerale Brand Bottled Water in the Jabodetabek Region - Shani Suryaningsih; Agung Surya Dwianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The competition in the Bottled Drinking Water (AMDK) industry in Indonesia, particularly in the Jabodetabek region, has shifted from price wars to a focus on reputation and product value. This phenomenon is highlighted by the significant rise in Le Minerale’s market share, which challenges the dominance of established market leaders. This study aims to analyze the influence of Brand Image and Brand Trust on consumer Purchase Decisions for Le Minerale products. This research employed a quantitative approach, collecting data from 120 respondents in the Jabodetabek region selected through purposive sampling. The data were analyzed using Multiple Linear Regression with SPSS version 26 software. The results indicate that both Brand Image and Brand Trust, whether tested partially or simultaneously, have a positive and significant influence on consumer purchase decisions. The coefficient of determination reveals that these two variables contribute 58.2% to the purchase decision, while the remaining percentage is influenced by other factors outside this study. These findings suggest that building a modern product image and maintaining strong consumer trust are key strategies for winning competition in the bottled water market.